P262 Prevelance of non-expandable lung in patients who had indwelling pleural catheter- a four year review. (December 2018) - Abi Musa Asa'ari, AKA; Marathe, M; Maddekar, N; Haris, M; Khan, S
Abstract : Introduction: Indwelling pleural catheters (IPC) have increasingly been used as a therapeutic option to manage recurrent pleural effusions. IPCs are the preferred method of management for symptomatic effusion with non-expandable lung (NEL). Aims and objectives: To understand the prevalance of NEL in patients who had IPC. Methods: We retrospectively reviewed patients requiring IPC insertion for management of recurrent pleural effusions looking at the proportion of patients with non-expandable lung (>25% of hemi thorax without expanded lung on plain chest radiograph), timing of IPC insertion from first appearance of clinically significant effusion, survival post-IPC insertion and the number of therapeutic procedures prior to IPC insertion. Results: Data on 123 IPCs inserted in 121 patients between 2013–2017 was available at the time of analysis (2 patients had bilateral IPCs). 11 IPCs were inserted for benign conditions. 60% of IPC patients had metastatic lung cancer. Effusion size is shown in table 1. 29.3% (n=36) had evidence of non-expandable lung (22 and 14 were noted after and before IPC insertion respectively). 50% of the NEL had metastatic lung cancer. 110 IPCs had pleural effusion present for a median of 59.5 days (IQR, 33–151.8) prior to IPC insertion. Of the 77% (n=85) patients who died, 36% had trapped lung. Median days from IPC insertion to death was 63 (IQR, 29–148). 17 patients are still alive whilst 8 were lost to follow up. Conclusion: 29% had Non-expanded lung from our cohort group. Median survival post IPC insertion was approximately 2 months. A third of IPC patients who died had NEL. The risk of NEL increased with longer duration of effusion but did not appear to have a significant relation to the effusion size. There is a need for a larger collaborative data to understand the true prevalence of NEL.